Transient Blindness in A Child with Dengue Shock Syndrome - Irwanto Irwanto; Soegeng Soegiyanto; Parwati Setiono Basuki; Wisnujono Soewono; Diany Yogiantoro (Paediatrica Indonesiana, 1997)
Dengue hemorrhagic fever (DHF) is characterized by acute fever associated With haemorrhagic diathesis and tendency to develop fatal shock (dengue shock syndrome). Signs and symptoms of DHF are generally secondary to plasma leakage and hemorrhage. Dengue shock syndrome (DSS) is a severe clinical manifestation of DHF usually as a consequence of severe plasma leakage. During tire last 5 years, there have been reports of DHF patients with unusual manifestations, including some patients with central nervous system (CNS) involvement We report a 5 year old DHF patient who experienced transient blindness, which was the first case found in Soetomo Hospital, Surabaya.